Neuroinfectious Disease OSCE Station - Penelope Smyth; Jeffrey Jirsch (Association of American Medical Colleges, 2014)
Abstract Introduction It has been stated that a headache is the most common neurological symptom. Identification of secondary headache syndromes is a critical skill for neurologists and neurology residents, especially in the emergency room setting; early recognition of encephalitis, especially herpes encephalitis, is crucial. Delayed diagnosis of herpes encephalitis with delayed treatment with acyclovir leads to increased morbidity and mortality. Due to this clinical importance, and in alignment with national training objectives, we created this station as part of a seven-station OSCE delivered to adult and pediatric neurology residents. Methods This is a one-station, performance-based assessment of resident competence in assessing headache, identifying secondary headache presentation, diagnosing and managing herpes simplex encephalitis through interpretation of a lab and imaging, with complication recognition, through a case presentation. Resident OSCE station instructions, examiner marking sheet, a PowerPoint presentation, and instructors' guide are included. This is primarily a summative assessment tool. Results Twenty-four senior neurology residents (PGY 3 to 5) were examined. Using a pass threshold of 70%, all residents passed the station. Resident scores ranged from 70.6% to 96.1% with a mean of 83.1% (SD 8.20%). Discussion Residents generally did well on recognizing secondary headache presentation. Residents recognized worrisome features on CSF findings and initiated prompt treatment. Knowledge of herpes encephalitis, prognosis, and possible complications was overall solid. Residents had the most difficulty interpreting imaging findings, especially MRI diffusion weighted and ADC map. Overall, residents recognized the neuro-critical situation with impending brain herniation and managed the complication successfully.